Efficacy and optimization of molecular techniques for sexing skeletonized human remains - Hildebrandt, Curtis J. B. (My University, 2003)
Forensic anthropologists and bioarchaeologists are often confronted with the problem of sex determination in poorly preserved, skeletonized, adult, human remains. This thesis tests the ability o f newly developed DNA methods to address this problem. Using a blind research design, four molecular DNA techniques - amelogenin, alphoid repeats, SRY (sex determining region o f the Y-chromosome) and Y-STRs (short tandem repeats) - are assessed for their ability to determine the sex o f 19 skeletons with known morphological and/or documented sex. The skeletons represent both historic and ancient human remains. The latter are from a Roman cemetery in the Dakhleh Oasis, Egypt (n=13), while the former are from historic 19^'’ century cemeteries in London, Ontario (n=4) and Thunder Bay, Ontario (n=l); as well as, an unidentified skeleton fi*om a forensic cold case (CFS file # A-475-95). It was hypothesized that the alphoid repeat technique should yield the best results due to their position near the chromosomal ends and the nature o f DNA degradation. The results show that although the alphoid repeats typed for all but one sample, the amelogenin had a superior performance, especially for the historic samples. The SRY method was very poor, appearing for only two samples, and the Y-STR method did not yield amplification at all. The latter was unexpected and disappointing, because it YSTRs have the potential to aid in male individuation in addition to its inherent ability to identify sex. The implications for both forensic and bioarchaeological research are far reaching. Based on the data from this thesis, two important conclusions emerge. The first is that the results of the amelogenin locus on 100-year-old samples are encouraging. This shows that even in samples with relatively high degradation, the sex o f an individual is still ascertainable and this is important for forensics, especially where cold cases are concerned. The second conclusion is that more research is definitely required given the poor performance o f the alphoid repeat and Y-STR methods. These include studies to determine more stringent contamination checks, such as mtDNA sequencing o f all samples yielding results for ancient DNA (aDNA).
Keywords: Sex determination (Genetic); Human remains (Archaeology); Cytological/molecular sex determination; Cellular biology; Ancient DNA